2017
DOI: 10.12968/hmed.2017.78.6.344
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards attrition among UK trainees in obstetrics and gynaecology

Abstract: Physician dissatisfaction in the workplace has consequences for patient safety. Currently in the UK, 1 in 5 doctors who enter specialist training in obstetrics and gynaecology leave the programme before completion. Trainee attrition has implications for workforce planning, organization of health-care services and patient care. The authors conducted a survey of current trainees' and former trainees' views concerning attrition and 'peri-attrition' - a term coined to describe the trainee who has seriously conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The 2017 national RCOG Workforce Survey has shown a 30% attrition rate during obstetrics and gynaecology (O&G) training. A questionnaire survey of O&G trainees in North London noted that 80% of respondents had considered leaving the specialty (which corresponded to 24% of regional trainees in the specialty). The main factors contributing to this were rota issues, undermining and the emotional burden of the specialty.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%
“…The 2017 national RCOG Workforce Survey has shown a 30% attrition rate during obstetrics and gynaecology (O&G) training. A questionnaire survey of O&G trainees in North London noted that 80% of respondents had considered leaving the specialty (which corresponded to 24% of regional trainees in the specialty). The main factors contributing to this were rota issues, undermining and the emotional burden of the specialty.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%
“…Maternity services are regularly subjected to negative reports in the media, further adversely impacting staff morale along with the escalating confrontational blame culture around the medicolegal landscape. These factors have led to growing attrition rates among trainees in Obstetrics and Gynaecology,11 reduced training time for those working in the area despite the little amendment to the length, scope or methods of education in our training programmes 12…”
Section: Working In Obstetrics and Gynaecologymentioning
confidence: 99%
“…National feedback on O&G training is regularly collected via the General Medical Council (GMC) Survey, the RCOG Training Evaluation Form (TEF) and the RCOG Trainee Attrition and Workforce Survey. These have identified the key reasons for trainee attrition as low morale and undermining, training processes and paperwork, support and supervision, work–life balance, NHS environment and job satisfaction . A recent study assessing factors that may reduce trainee attrition identified the following key themes: being valued as an individual, flexibility and predictability, standardisation and transparency in processes to promote fairness, access to quality support, and learning‐focused training .…”
Section: Introductionmentioning
confidence: 99%